2021
DOI: 10.3390/app11188702
|View full text |Cite
|
Sign up to set email alerts
|

Litholytic Activities of Natural Bioactive Compounds and Their Mechanism Insights

Abstract: Urolithiasis is a disease characterized by the formation of stones, which are crystalline accretions that form in the urinary tract from minerals dissolved in the urine. Moreover, it is considered to be a complex and multifactorial disease, requiring treatment. Unfortunately, current treatments are insufficient or may induce several side effects. In fact, medicinal plants are among the anti-litholytic treatments that are strongly recommended by many studies. Indeed, these natural resources contain bioactive mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…This result explains the low effect of gum arabic extract (43%) and the significant inhibitory effect of Argania spinosa extract (83%) on the nucleation event. Phenolic acids were one of the secondary metabolites contained in Argania spinosa (L.) press-cake in our study, and are known for their anti-crystallization properties [23]. Other phytomolecules can contribute and cannot be excluded from anti-urolithiatic activity, such as succinic acid and catechin [20][21][22][23][24][25][26][27][28], which were identified in the Argania spinosa extract by GC/MS analysis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This result explains the low effect of gum arabic extract (43%) and the significant inhibitory effect of Argania spinosa extract (83%) on the nucleation event. Phenolic acids were one of the secondary metabolites contained in Argania spinosa (L.) press-cake in our study, and are known for their anti-crystallization properties [23]. Other phytomolecules can contribute and cannot be excluded from anti-urolithiatic activity, such as succinic acid and catechin [20][21][22][23][24][25][26][27][28], which were identified in the Argania spinosa extract by GC/MS analysis.…”
Section: Discussionmentioning
confidence: 95%
“…Phenolic acids were one of the secondary metabolites contained in Argania spinosa (L.) press-cake in our study, and are known for their anti-crystallization properties [23]. Other phytomolecules can contribute and cannot be excluded from anti-urolithiatic activity, such as succinic acid and catechin [20][21][22][23][24][25][26][27][28], which were identified in the Argania spinosa extract by GC/MS analysis. In addition, several phenolic acids were identified in the Argania spinosa extract.…”
Section: Discussionmentioning
confidence: 95%
“…We noted that the extracts had a variable content of polyphenols and flavonoids. Secondly, to study the antilithiasis activity we have chosen the extract of dichloromethane which is rich in flavonoids (2446, 064 ± 63, 606) and the aqueous extract which is rich in polyphenols (15270, 751 ± 290, 419) and also the fraction of alkaloids (1.26%), this choice was based on recent studies that have shown that some metabolites such as saponins, flavonoids, polyphenols, and polysaccharides contribute significantly to the antiurolithiatic activity 30,[37][38][39] .…”
Section: Results: Phytochemicalmentioning
confidence: 99%
“…The-oxygen and nitrogen atoms present in polyphenols fraction (Resveratrol and Pyrogallol), flavonoids fraction (Quercetin, kaempferol), and alkaloids fraction (Lotusanine A, B, Sanjoinenine, Sanjoinine F, and Frangufoline) respectively can complex free Ca 2+ in solution, increase Ca 2+ enrichment and form high-energy interface on of these metabolites surface, so the chelating ability of Ca 2+ was enhanced depending on the number of these atoms. Consequently, the calcium ion amount bound to the oxalate ion (Ox 2− ) decreased which inhibited the formation of calcium oxalate stones 39,40 . According to the study of Saha S et al 41 the effect of phenolic compounds on the formation of urolithiasis of calcium oxalate type could result not only from the 'electrostatic interaction between polyphenols and calcium ions but also from the interaction of type hydrogen between polyphenolic compounds and oxalate ions.…”
Section: Results: Phytochemicalmentioning
confidence: 99%